2003
DOI: 10.1016/s0899-3467(07)60080-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isometric Handgrip Exercise Training on Resting Hemodynamics: A Pilot Study

Abstract: (J Chiropr Med 2003;27:153-156)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Following the removal of duplicates, 1789 studies were screened (titles and abstracts) down to 41 potentially eligible studies. Full-text review led to the removal of 15 articles for reasons of not reporting pre- to post-intervention change in blood pressure [2125], research was an acute assessment of handgrip-induced real-time fluctuations to BP [26, 27], research was a case study [28], research was a synthesis of other articles [29], publication was a commentary [30], and only MAP was reported with no way of extracting SBP and diastolic BP (DBP) [3135]. Therefore, 26 studies were included in this review (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following the removal of duplicates, 1789 studies were screened (titles and abstracts) down to 41 potentially eligible studies. Full-text review led to the removal of 15 articles for reasons of not reporting pre- to post-intervention change in blood pressure [2125], research was an acute assessment of handgrip-induced real-time fluctuations to BP [26, 27], research was a case study [28], research was a synthesis of other articles [29], publication was a commentary [30], and only MAP was reported with no way of extracting SBP and diastolic BP (DBP) [3135]. Therefore, 26 studies were included in this review (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐seven studies reported the chronic changes in resting blood pressure after isometric handgrip training (Ahmed et al, 2019; Allen et al, 2003; Alomari et al, 2010; Baddeley‐White et al, 2019; Badrov, Bartol, et al, 2013; Badrov, Horton, et al, 2013, 2016; Bank et al, 1998; Baross et al, 2017; Bentley et al, 2018; Cahu Rodrigues et al, 2020; Carlson et al, 2016; Correia et al, 2020; Dempster et al, 2018; Dobrosielski et al, 2009; Farah et al, 2018; Gandhi, 2016; Garg et al, 2014; Goessler et al, 2018; Herrod et al, 2019; Hess et al, 2016; Howden et al, 2002; Lara et al, 2015; McGowan et al, 2006; McGowan, Levy, et al, 2007; McGowan, Visocchi, et al, 2007; Millar et al, 2007, 2008, 2013; Mortimer & McKune, 2011; Ogbutor et al, 2019; Okamoto et al, 2020; Pagonas et al, 2017; Peters et al, 2006, Punia & Kulandaivelan, 2020; Ray & Carrasco, 2000; Saito et al, 2009; Sinoway et al, 1996; Somani et al, 2017, 2018; Somers et al, 1992; Souza et al, 2020; Stiller‐Moldovan et al, 2012; Taylor et al, 2003; Wiley et al, 1992; Yamagata & Sako, 2020; Zhang, 2003) (Table 2). In total, 22 studies included a nonexercise control group, three studies included a sham‐control group, one study provided a lifestyle modification program to both treatment and control groups, and 21 studies only had one or multiple isometric handgrip training groups.…”
Section: Methodsmentioning
confidence: 99%